Adaptation, mitigation and risk-taking in climate policy - Heike Auerswald; Kai A. Konrad; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2011)
The future consequences of climate change are highly uncertain. Today, the exact size of possible future damages are widely unknown. Governments try to cope with these risks by investing in mitigation and adaptation measures. Mitigation aims at a reduction of greenhouse gas emissions whereas adaptation reduces the follow-up costs of climate change. In contrast to the existing literature, we explicitly model the decision of risk-averse governments on mitigation and adaptation policies. Furthermore we also consider the interaction of the two strategies. Mitigation efforts of a single country trigger crowding out as other countries will reduce their mitigation efforts. We show that, under fairly mild conditions, a unilateral increase in mitigation efforts of a single country can even increase global emissions. In contrast, a unilateral commitment to large adaptation efforts benefits the single country and may reduce the global risk from climate change at the expense of other countries.
Keywords: Q54; Q58; 330; climate change; adaptation; mitigation; risk-taking; Klimaveränderung; Umweltpolitik; Immissionsschutz; Politische Entscheidung